2011
DOI: 10.1113/expphysiol.2010.054882
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the purinergic system in central cardiovascular modulation at the level of the nucleus ambiguus of anaesthetized rats

Abstract: Anatomical studies have demonstrated the existence of purinergic P2 receptors in the nucleus ambiguus (NA), a site containing cardiac vagal motoneurons. However, very little is known about the functional role of these receptors in central cardiac vagal regulation. The aims of our study were to evaluate the following: (1) the blood pressure and heart rate responses following purinoceptor activation within the NA; (2) the role of purinoceptors and excitatory amino acid (EAA) receptors in mediating the cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
4
0
2
Order By: Relevance
“…Importantly, ATP has been shown to act as a cotransmitter with glutamate (Braga et al 2007;Pankratov et al 1998Pankratov et al , 2002Passamani et al 2011;Scislo and O'Leary 2000), and we recently showed that ATP-evoked sympathoexcitatory responses within the PVN were blunted in the presence of ionotropic glutamate receptor blockade (Ferreira-Neto et al 2013). Similar to this previous study, we found here that the ionotropic glutamatergic receptor antagonist KYN abolished the ATP-evoked increase in firing activity in PVN sympathetic neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, ATP has been shown to act as a cotransmitter with glutamate (Braga et al 2007;Pankratov et al 1998Pankratov et al , 2002Passamani et al 2011;Scislo and O'Leary 2000), and we recently showed that ATP-evoked sympathoexcitatory responses within the PVN were blunted in the presence of ionotropic glutamate receptor blockade (Ferreira-Neto et al 2013). Similar to this previous study, we found here that the ionotropic glutamatergic receptor antagonist KYN abolished the ATP-evoked increase in firing activity in PVN sympathetic neurons.…”
Section: Discussionsupporting
confidence: 80%
“…The suggestion that CVMs from the dorsal motor vagal nucleus might be selectively activated by cardiopulmonary inputs (Daly and Kirkman, 1989; Jones and Daly, 1997) no longer appears tenable (Jones, 2001; Wang et al, 2000). The bradycardia evoked by stimulation of cardiopulmonary afferents in the rat is attenuated after bilateral microinjection of P2X antagonist in the nucleus ambiguus suggesting CVMs in this region are also activated by this input via release of purines (Passamani et al, 2011). Interestingly, an essential role for CVMs in the dorsal motor vagal nucleus has recently been proposed for the cardioprotective effects of remote ischemic preconditioning in this species (Mastitskaya et al, 2012) which appears to be independent of effects on heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the RVLM, Ralevic et al [53] and Horiuchi et al [54] have shown that there does not appear to be an interplay between purinergic and glutamatergic systems. However, in other brain nuclei, several studies have demonstrated that ATP and glutamate can function as cotransmitters [39,41,[55][56][57]. For example, in nucleus of the solitary tract (NTS) neurons, the fast responses to stimulation of P2X receptors are mediated via glutamatergic ionotropic mechanisms [58].…”
Section: Discussionmentioning
confidence: 99%